Semiochemical responsive olfactory sensory neurons are sexually dimorphic and plastic - Vihani, Aashutosh (eLife, 2020)
Understanding how genes and experience work in concert to generate phenotypic variability will provide a better understanding of individuality. Here, we considered this in the main olfactory epithelium, a chemosensory structure with over a thousand distinct cell types in mice. We identified a subpopulation of olfactory sensory neurons, defined by receptor expression, whose abundances were sexually dimorphic. This subpopulation of olfactory sensory neurons was over-represented in sex-separated mice and robustly responsive to sex-specific semiochemicals. Sex-combined housing led to an attenuation of the dimorphic representations. Single-cell sequencing analysis revealed an axis of activity-dependent gene expression amongst a subset of the dimorphic OSN populations. Finally, the pro-apoptotic gene Baxwas necessary to generate the dimorphic representations. Altogether, our results suggest a role of experience and activity in influencing homeostatic mechanisms to generate a robust sexually dimorphic phenotype in the main olfactory epithelium.